2021
DOI: 10.1071/wf21106
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution fire danger forecast for Poland based on the Weather Research and Forecasting Model

Abstract: Due to climate change and associated longer and more frequent droughts, the risk of forest fires increases. To address this, the Institute of Meteorology and Water Management implemented a system for forecasting fire weather in Poland. The Fire Weather Index (FWI) system, developed in Canada, has been adapted to work with meteorological fields derived from the high-resolution (2.5 km) Weather Research and Forecasting (WRF) model. Forecasts are made with 24- and 48-h lead times. The purpose of this work is to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The weather research and forecasting (WRF) model, an open-source atmospheric simulation model that integrates regional land-atmosphere phenomena [19], can overcome many limitations of the observed stations in providing information relevant to local and regional fire management at a finer spatial scale. WRF has widely been applied in fire research by providing weather input data of drought-fire models, such as in Australia [20], Poland [21], and the United States [22]. In Indonesia, the applicability of the WRF of fire assessment has been initiated recently in Sumatra peatlands [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The weather research and forecasting (WRF) model, an open-source atmospheric simulation model that integrates regional land-atmosphere phenomena [19], can overcome many limitations of the observed stations in providing information relevant to local and regional fire management at a finer spatial scale. WRF has widely been applied in fire research by providing weather input data of drought-fire models, such as in Australia [20], Poland [21], and the United States [22]. In Indonesia, the applicability of the WRF of fire assessment has been initiated recently in Sumatra peatlands [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that in Mediterranean ecosystems, climate variability is the leading factor regarding wildfire seasonality and fuel layer flammability [48]. Increased fuel flammability due to prolonged drought and higher overall temperatures is considered one of the main ecosystem responses to climate change [49].…”
Section: Study Regionmentioning
confidence: 99%
“…The FWI, based on temperature, relative humidity, wind speed and precipitation (Van Wagner 1987;Anderson 2005;Mandal et al 2021) was calculated daily using the gridded and station data. The median FWI values were calculated for each location over the year-long period.…”
Section: Vector Wind Change and Fire Weather Indexmentioning
confidence: 99%